Synthesis and Characterization of Non‐Aqueous [TcXM‐PW11O39]n– with M = O, N: Comparing TcV and TcVI in Metal Oxide Matrices. Issue 45 (26th November 2019) - Burton‐Pye, Benjamin P.; Dembowski, Mateusz; Lukens, Wayne W.; Cruz, Anthony; Althour, Alrasheed; Lopez, Gustavo E.; Salcedo, Ramsey; Gallagher, Colleen M. B.; McGregor, Donna; Francesconi, Lynn C.
Abstract : Technetium‐99, a prevalent by‐product of the nuclear fuel cycle, is a transition metal with 9 accessible oxidation states and a half‐life of 2.1 × 10 5 years. 99 Tc VII has been found in the environment surrounding National Lab sites and fuel reprocessing centers, and its separation and long‐term storage is complicated by its extensive redox chemistry. In our prior work we have reported the synthesis and reduction of Tc V O to Tc IV O in α1 ‐ and α2 ‐Wells–Dawson P2 W17 O61 10– polyoxometalates and reported on the polyoxometalate features that promote reduction and stabilization. In this work we report on the oxidation state stabilization of Tc V O, Tc VI O and Tc VI N within the α‐Keggin PW11 O39 7– polyoxometalate. Both Density Functional Theory and experimental results show that Tc in TBA4 [Tc VI N‐PW11 O39 ] can be reduced to Tc V, but any subsequent electrons reduce the tungsten framework of the polyoxometalate. TBA4 [Tc V O‐PW11 O39 ] however, can be theoretically reduced down to Tc I before reduction of the polyoxometalate occurs. Abstract : We report on the oxidation state stabilization of technetium in α‐PW11 O39 7 – with O and N ancillary ligands. Our results suggest that Tc in the TcN complex generally favors higher oxidations states (Tc V and above), while the Tc within the TcO complex can access a larger range of oxidation states, theoretically all the way down to the Tc I .